2017
DOI: 10.1016/j.ajo.2017.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Residential Pesticide Exposures in Pregnancy and the Risk of Sporadic Retinoblastoma: A Report From the Children's Oncology Group

Abstract: Purpose To examine whether parental pesticide exposure contributes to the development of sporadic retinoblastoma. Design Case-control study. Methods Data were collected by a large multicenter study of sporadic retinoblastoma in which parents of 99 unilateral and 56 bilateral age matched case-control pairs were interviewed by telephone. Retrospective exposure information was collected on the type, location, timing and frequency of residential pesticide use. We used conditional logistic regression analyses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…For non-occupational exposures, one study reporting on household pesticide use found the risk for non-heritable unilateral retinoblastoma to be increased among mothers who were exposed to insect or garden sprays during pregnancy, although CIs were wide (OR: 2.7; 95% CI: 0.6 to 15.6) 35. We recently reported an increased risk of unilateral disease associated with parental use of home insecticides as well as home use of professional lawn or landscape services 36. Two studies examined the association between ionising radiation exposure in parents and the development of retinoblastoma in offspring, and both found that mothers who had high gonadal radiation exposure were at increased risk of having a child with sporadic bilateral retinoblastoma, although only the larger, more rigorous study was sufficiently powered 8 35…”
Section: Discussionmentioning
confidence: 99%
“…For non-occupational exposures, one study reporting on household pesticide use found the risk for non-heritable unilateral retinoblastoma to be increased among mothers who were exposed to insect or garden sprays during pregnancy, although CIs were wide (OR: 2.7; 95% CI: 0.6 to 15.6) 35. We recently reported an increased risk of unilateral disease associated with parental use of home insecticides as well as home use of professional lawn or landscape services 36. Two studies examined the association between ionising radiation exposure in parents and the development of retinoblastoma in offspring, and both found that mothers who had high gonadal radiation exposure were at increased risk of having a child with sporadic bilateral retinoblastoma, although only the larger, more rigorous study was sufficiently powered 8 35…”
Section: Discussionmentioning
confidence: 99%
“…Paternal work in agriculture or as a pesticide applicator has been examined as a risk factor for retinoblastoma or among childhood eye cancers (of which retinoblastoma accounts for over 90%) (13)(14)(15)(16)(17); however, only two of these studies found positive associations (10,18). These positive associations are further supported by findings of increased retinoblastoma risk when parents use insecticides in their homes (19,20). Other occupational studies have reported increased risk of retinoblastoma among children of fathers who are electrical workers (21), exposed to paints (22), or employed in the metal industry (11,12).…”
Section: Introductionmentioning
confidence: 71%
“…The RB1 gene inactivation occurs during DNA replication in proliferating retinal progenitor cells, and retinal progenitor cell proliferation occurs only in the fetal retina. Since genetic inactivation is required in both copies of RB1 to induce retinoblastoma, it has been proposed that prenatal exposure to pesticides could act as a second hit [72].…”
Section: Retinoblastomamentioning
confidence: 99%